Electrolyte membrane and water electrolysis device using the same
A polymer electrolyte membrane with controlled molecular weight and distribution, integrated with a polyarylene polymer and pore-filling structure, addresses the issues of film-forming properties and alkali durability in anion exchange membrane type water electrolysis, ensuring efficient hydrogen generation.
Patent Information
- Application Number
- JP2023217509
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2025-07-07
AI Technical Summary
Existing electrolyte membranes for anion exchange membrane type water electrolysis methods lack sufficient film-forming properties and alkali durability, necessitating improved materials for efficient hydrogen generation.
The development of a polymer electrolyte membrane with specific weight-average molecular weight (Mw) and molecular weight distribution (Mw/Mn) ranges, combined with a pore-filling structure using a polyarylene polymer, enhances film-forming properties and alkali durability.
The proposed electrolyte membrane exhibits excellent solubility, enabling effective film formation and high alkali durability, thereby facilitating efficient hydrogen generation in anion exchange membrane type water electrolysis.
Smart Images

Figure 2025100998000001 
Figure 2025100998000002 
Figure 2025100998000003
Abstract
Description
Technical Field
[0001] The present invention relates to an electrolyte membrane using a polymer excellent in film-forming properties and alkali durability. More specifically, the present invention provides an electrolyte membrane particularly excellent in an anion exchange membrane type water electrolysis method.
Background Art
[0002] Electrolyte membranes are used in various fuel cells such as solid polymer fuel cells and solid alkaline fuel cells, and various electrolysis technologies such as water electrolysis. The electrolyte membrane is required to have excellent ionic conductivity and durability that can withstand long-term use.
[0003] Among water electrolysis methods, the anion exchange membrane type water electrolysis method (AEMWE method) has been proposed as a technology to replace the cation exchange membrane type water electrolysis method and the alkaline water electrolysis method, and has attracted attention in recent years. In this method, an anion exchange membrane (AEM) is used as a membrane separating the anode chamber and the cathode chamber, and pure water or an alkaline aqueous solution is supplied as anolyte to the anode chamber. Although pure water or an alkaline aqueous solution may be supplied as catholyte to the cathode chamber, it is also possible to use a dry cathode type electrolytic cell in which no catholyte is supplied to the cathode chamber. In the case of this dry cathode type, water penetrates from the anode chamber to the cathode chamber through the anion exchange membrane, so that water is supplied to the cathode chamber, and hydroxide ions are generated together with hydrogen gas from water by a cathode reaction in the cathode chamber.
[0004] As the electrolyte membrane for this AEMWE, Patent Document 1 discloses a proton conductive material for an electrolyte membrane having high swelling resistance and a high proton conductivity with a high density of ion exchange groups, which has a specific hydrophilic part and a specific hydrophobic part, and has a repeating unit containing a specific cyclic compound in at least one of the hydrophilic part and the hydrophobic part. The proton conductive material has a structure in which the hydrophilic part and the hydrophobic part are bonded via an ether bond.
[0005] In Patent Document 2, a polymer having a structure in which a divalent aromatic group having an ionic functional group and a spirobifluorene skeleton are alternately repeated is disclosed as an anion-conductive polymer for an electrolyte membrane that is excellent in chemical durability and solubility in a solvent.
[0006] In Patent Document 3, a report on an anion-conductive polymer for an electrolyte membrane and an electrolyte membrane using the same, which are excellent in chemical durability and ionic conductivity, has been made. However, the described anion-conductive polymer is produced by a manufacturing method that is not suitable for production because it uses a halogen-based solvent with a high environmental load, and a manufacturing method for a material for an electrolyte membrane with higher productivity is required.
Prior Art Documents
Patent Documents
[0007]
Patent Document 1
Patent Document 2
Patent Document 3
Summary of the Invention
Problems to be Solved by the Invention
[0008] In view of the above circumstances, the present invention proposes an electrolyte membrane, particularly an electrolyte membrane useful for an anion exchange membrane type water electrolysis method. Specifically, it aims to provide an electrolyte membrane excellent in film-forming properties and alkali durability.
Means for Solving the Problems
[0009] As a result of intensive studies, the present inventors have found that a polymer having a specific Mw (weight average molecular weight) can solve the above problems. That is, the present invention relates to the following 1) to 10). 1) An electrolyte membrane using a polymer that satisfies the following formula (Equation 1) for Mw (weight-average molecular weight).
Equation
Equation
Equation
Chemical Formula
Advantages of the Invention
[0010] According to the present invention, it is possible to realize an electrolyte membrane having excellent solubility, that is, good film-forming properties, and excellent alkali durability.
Embodiments for Carrying Out the Invention
[0011] The polymer used in the electrolyte membrane of the present invention is characterized by satisfying the above formula (Equation 1). [Mw (weight average molecular weight)] In the present invention, Mw means the weight average molecular weight and can be measured by GPC (gel permeation chromatography) under the following conditions. Apparatus: EcoSEC-Elite (manufactured by Tosoh Corporation) Column: TSKgel SuperMultipore HZ-M 3 columns (manufactured by Tosoh Corporation) Measurement temperature: 40 °C Sample solution: 0.12 wt% THF solution Mobile phase: THF Solution injection volume: 10 μL Flow rate: 0.4 mL / min Detector: Refractive index detector Reference substance: Standard polystyrene (TSKgel standard polystyrene) (manufactured by Tosoh Corporation, 8 points (Mw: 1110000, 397000, 189000, 37200, 15700, 5430, 3120, 589))
[0012] In the present invention, the lower limit of the Mw of the polymer is 170,000, more preferably 180,000, 190,000, 200,000, 220,000 in order, and particularly preferably 240,000. Also, the upper limit of the Mw of the polymer is 400,000, more preferably 380,000, 360,000, 350,000, 340,000, 320,000, 300,000 in order, and particularly preferably 280,000. Therefore, most preferably, the Mw of the polymer is 240,000 or more and 280,000 or less.
[0013] The polymer used for the electrolyte membrane of the present invention more preferably satisfies a specific molecular weight distribution, that is, Mw / Mn satisfies the above formula (Equation 2). The lower limit of Mw / Mn is 4.00, more preferably 4.50, 5.00, 5.50, 5.80 in order, and particularly preferably 6.00. Also, the upper limit of Mw / Mn is 9.00, more preferably 8.50, 8.00, 7.50, 7.00 in order, and particularly preferably 6.90. Therefore, most preferably, Mw / Mn is 6.00 or more and 6.90 or less.
[0014] The polymer used for the electrolyte membrane of the present invention more preferably satisfies the above formula (Equation 3). [Mn (number average molecular weight)] In the present invention, Mn means the number average molecular weight and can be measured using GPC. The measurement conditions may be the same as those used for the measurement of the above Mw. In the present invention, the lower limit of the Mn of the polymer is preferably 30,000, more preferably 32,000, 35,000 in order, and particularly preferably 36,000. Also, the upper limit of the Mn of the polymer is preferably 70,000, more preferably 60,000, 55,000, 45,000 in order, and particularly preferably 40,000. Therefore, most preferably, the Mn of the polymer is 36,000 or more and 40,000 or less.
[0015] [Pore-filling membrane] The electrolyte membrane of the present invention preferably has a pore-filling membrane structure in which a porous base material is used as the base film and the above polymer is filled. By adopting such a configuration, mechanical strength can be imparted to a polyarylene polymer excellent in chemical durability. The porous base material is a base material having pores capable of holding a polymer. From the viewpoint of improving ionic conductivity, it is preferable that at least a part of the pores form through-holes. In terms of imparting mechanical strength, the form of the base material is preferably a non-woven fabric or a porous film, and more preferably a porous film. The porosity of the porous base material (= volume of voids / bulk volume × 100 (%)) is preferably 30 to 95%, more preferably 40 to 80%, and still more preferably 45 to 70% from the viewpoint of achieving both mechanical strength and ionic conductivity. The film thickness of the porous base material is preferably 5 to 200 μm, more preferably 7 to 100 μm, and still more preferably 10 to 50 μm from the viewpoint of achieving both mechanical strength and ionic conductivity. In addition, the pore diameter of the porous base material is preferably 10 to 10,000 nm, more preferably 10 to 1,000 nm in terms of average diameter, from the viewpoints of filling and holding the polyarylene polymer and mechanical strength. From the viewpoints of chemical durability, particularly stability in alkali, the material of the porous base material is preferably a polyolefin-based porous base material. Also, using a polyolefin-based porous base material has the merit that a polyarylene polymer, especially a high molecular weight polyarylene polymer having a weight average molecular weight of 100,000 or more, is easily filled. Among polyolefin-based porous base materials, from the viewpoints of mechanical strength, chemical resistance, etc., polyethylene porous base materials, polypropylene porous base materials, or polytetrafluoroethylene porous base materials are particularly preferable. Among them, a polyethylene porous base material is preferably an ultra-high molecular weight polyethylene (for example, having a weight average molecular weight of 1,000,000 or more) porous base material.
[0016] As a method for manufacturing a pore-filling film, for example, a method of applying a polyarylene polymer to a porous substrate and drying it can be mentioned. As a method for applying a polyarylene polymer to a porous substrate, for example, a method using a solution of a polyarylene polymer and methods such as dipping, spraying, spin coating, and bar coating can be mentioned. After infiltrating a polyarylene polymer solution into the porous substrate and then drying it, a pore-filling film can be obtained. Note that the fact that the porous substrate is filled with a polyarylene polymer can be confirmed, for example, by Raman analysis.
[0017] [Structure and Manufacturing Method of Polymer] The polymer used in the electrolyte membrane of the present invention is preferably a polyarylene polymer. By using a polyarylene polymer, an electrolyte membrane excellent in chemical durability can be obtained. Furthermore, since the polyarylene polymer imparts excellent ionic conductivity to the pore-filling film, a polymer having a structural unit represented by the following general formula (1) (hereinafter, also referred to as polymer (A)) is preferable. [Chemical Formula 1] TIFF2025100998000005.tif21153However, Ar 1 is an aromatic group having an ion-exchange group or a group in which aromatic rings having ion-exchange groups are linked via a single bond, and a plurality of Ars 1 may be the same or different, Ar 2 is an aromatic group having no ion-exchange group or a group in which two or more aromatic rings having no ion-exchange group are linked via a single bond or a spiro atom, and a plurality of Ars 2 may be the same or different, Ar 1 The aromatic ring of and Ar 2 The aromatic ring of is linked via a single bond.
[0018] Polymer (A) is a polymer having two or more of the above structural units (1), and Ar having an ion-exchange group 1 And Ar having no ion-exchange group2 has an alternately arranged structure. Ar 1 The aromatic group that has and Ar 2 The aromatic groups that have are bonded by a single bond to form the main chain. There are no etheric oxygen (-O-), sulfonyl (-S(=O)2-), or carbonyl (-C(=O)-) skeletons in the main chain skeleton, and it is excellent in chemical durability, particularly alkali durability. Here, the aromatic ring refers to the aromatic ring that constitutes the main chain, and the aromatic ring that constitutes the main chain may further have an aromatic ring as a substituent. The aromatic ring that constitutes the main chain and the aromatic ring that is possessed as a substituent (side chain) are distinguished.
[0019] Ar 1 is an aromatic group having an ion-exchange group or a group in which aromatic rings having ion-exchange groups are linked via a single bond. Note that the ion-exchange group refers to a functional group having dissociability and capable of ion exchange.
[0020] When imparting proton conductivity to the polymer (A), the ion-exchange group is preferably an acidic group, and among acidic groups, a sulfonic acid group (-SO3H group), a phosphoric acid group (-H2PO4 group), or a carboxylic acid group (-COOH group) is preferably used, and a sulfonic acid group is more preferably used. Note that the H of the above acidic group may be dissociated or may be substituted with an alkali metal ion, an alkaline earth metal ion, or the like.
[0021] When imparting anionic conductivity to the polymer (A), the ion-exchange group is preferably a quaternary ammonium group or an imidazolium group, and more preferably a quaternary ammonium group. From the viewpoint of further alkali durability, the quaternary ammonium group is preferably a quaternary alkylammonium group. The quaternary alkylammonium group includes those in which the alkyl groups bonded to the nitrogen atom are bonded to form a ring structure, and may be, for example, an azadamantyl group, a quinuclidinium group, etc. Preferred specific examples of the above quaternary ammonium group include groups represented by the following formulas (e-1) to (e-8). Preferred specific examples of the imidazolium group include a group represented by the following formula (f-1), and further, a group represented by the following formula (f-2) or a group represented by the following formula (f-3) is more preferred.
[0022] [Chemical formula] In the formula, R e is each independently a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms, and R f is each independently a hydrogen atom, a linear or branched alkyl group having 1 to 4 carbon atoms, or an aromatic group which may have a substituent, and A - is a monovalent or divalent or higher anion, and when there are a plurality of R e or R f , the plurality of R e or R f may be the same or different from each other. The wavy line in the formula indicates a bond bonded to the aromatic ring side constituting the main chain in Ar 1 .
[0023] Specific examples of the alkyl group in the above R e include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a cyclohexyl group, etc. Specific examples of the alkyl group in the above R f include a methyl group, an ethyl group, a propyl group, a butyl group, etc. Also, R fExamples of the aromatic group include a phenyl group, etc., and examples of the substituent of the phenyl group include an alkyl group having 1 to 6 carbon atoms, etc.
[0024] The above A - is preferably an inorganic anion, such as chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - ), hydrogen carbonate ion (HCO3 - ), carbonate ion (CO3 2- ), hydroxide ion (OH - ), sulfate ion (SO4 2- ), chlorate ion (ClO3 - ), nitrate ion (NO3 - ), cyanide ion (CN - ), hydrogen sulfite ion (HSO3 - ), bromate ion (BrO3 ― ), fluoride ion (F - ), etc. Among them, preferably hydroxide ion (OH - ), bromide ion (Br - ), bromate ion (BrO3 ― ), chloride ion (Cl - ), hydrogen carbonate ion (HCO3 - ), carbonate ion (CO3 2- ), and particularly preferably hydroxide ion (OH - ), bromide ion (Br - ), chloride ion (Cl - ), hydrogen carbonate ion (HCO3 - ), carbonate ion (CO3 2- ).
[0025] The above ion exchange group is Ar 1It may be directly bonded to the aromatic ring constituting the main chain in [substance], further have a linking group, and may be bonded to the aromatic ring constituting the main chain through the linking group. Here, the linking group represents an organic group that links the acidic group, quaternary ammonium group, or imidazolium group possessed by the ion exchange group and the aromatic ring constituting the main chain. As the organic group, a linear or branched alkylene group is preferable, and among them, a linear alkylene group is more preferable. The number of carbon atoms of the alkylene group can be appropriately adjusted according to the physical properties required for the polymer (A). For example, by setting the number of carbon atoms of the alkylene group to 20 or less, preferably 16 or less, more preferably 12 or less, the ion exchange group capacity of the polymer (A) increases. On the other hand, by setting the number of carbon atoms of the alkylene group to 2 or more, preferably 4 or more, more preferably 6 or more, it has excellent solubility and swelling resistance, and it becomes easier to fill the polymer (A) into a porous substrate. Ar 1 In [substance], the number of ion exchange groups per aromatic ring constituting the main chain may be 1 or more, and from the viewpoints of ion conductivity and polymer stability, 1 to 2 are preferable.
[0026] Ar 1 As the aromatic ring constituting the main chain in [substance], in addition to the benzene ring, a condensed ring such as a naphthalene ring or an anthracene ring may be used, or a heterocyclic ring (for example, thiophene, etc.) containing an oxygen atom (O), a nitrogen atom (N), or a sulfur atom (S) may also be used. Further, these aromatic rings may have a structure linked by a single bond. Examples of the structure in which a plurality of rings are linked by a single bond include biphenyl, terphenyl, fluorene, and the like.
[0027] Ar 1The aromatic ring constituting the main chain in [the compound] may further have substituents other than the ion-exchange group in addition to the above ion-exchange group. Examples of such substituents include an alkyl group having 1 to 20 carbon atoms which may have a substituent, a phenyl group which may have a substituent, a halogeno group, etc. Specific examples of the above alkyl group include alkyl groups such as a methyl group, an ethyl group, a propyl group, an n-butyl group, a tert-butyl group, a pentyl group, a hexyl group, an octyl group, etc., and may have a phenyl group, a halogeno group, etc. as a substituent. Further, examples of the substituent which the above phenyl group may have include an alkyl group having 1 to 6 carbon atoms, a halogeno group, etc. Further, examples of the above halogeno group include a fluoro group, a chloro group, a bromo group, an iodo group, etc.
[0028] From the viewpoints of excellent mechanical strength, chemical durability, and ion conductivity, the Ar of the polymer (A) 1 is preferably a group represented by any one of the following formula (a-1) to the following formula (a-10). In addition, a plurality of Ars in the polymer 1 may be the same as or different from each other.
[0029] [Chemical formula] However, R a is each independently a hydrogen atom, an ion-exchange group, or a substituent having no ion-exchange group, and a plurality of Rs a may be the same as or different from each other, and at least one of the Rs a is an ion-exchange group. The wavy line indicates a bond that binds to Ar 2 .
[0030] Ar 2 The aromatic ring constituting the main chain that Ar has includes the same ones as the above Ar 1 and groups linked via a spiro atom. Further, the aromatic ring in Ar 2 may have other substituents other than the anion-exchange group. Examples of the other substituents include the above Ar 1Examples thereof include the same substituents as those other than the ion-exchange group in [reference]. Ar 2 Examples of the group in which two or more aromatic rings in [reference] are linked via a spiro atom include, for example, the group represented by the following formula (c1). Examples of the group in which two or more aromatic rings are linked via a single bond include, for example, the groups represented by the following formulas (c2) to (c4). The wavy line indicates the bond to Ar 1 . From the viewpoint of the filling property of the polymer into the porous substrate, Ar 2 preferably does not have a spiro atom.
[0031]
Chemical formula
[0032] The weight-average molecular weight of the polymer (A) can be appropriately adjusted from the viewpoints of chemical durability and ease of filling into pores, and can be, for example, in the range of 10,000 to 1,000,000. From the viewpoint of chemical durability, it is preferably 30,000 or more, and more preferably 100,000 or more. In particular, when the porous substrate is a polyolefin-based porous substrate, even if the weight-average molecular weight of the polymer (A) is 100,000 or more, it is easy to fill into the pores. The weight-average molecular weight is a value in terms of polystyrene measured by GPC (gel permeation chromatography).
[0033] The polymer (A) may consist only of the structural unit represented by the general formula (1) (also referred to as the structural unit (1)), or may have other structural units. Examples of the other structural units include, for example, a structure in which an anion-exchange group is not introduced into Ar 1 in the structural unit (1). It may also contain other structures that can occur during synthesis.
[0034] Polymer (A) is preferably, among others, the following polymers (A1) to (A4). From the viewpoint of the filling property of the polymer into the porous substrate, among others, polymer (A2), polymer (A3) or polymer (A4) is preferable, polymer (A2) or polymer (A3) is more preferable, and further, from the viewpoints of the filling property, mechanical strength and chemical durability of the polymer, polymer (A3) is preferable. These polymers will be described in detail below.
[0035] ·Polymer (A1) Polymer (A1) has a repeating unit represented by the following general formula (1-a).
[0036]
Chemical formula
[0037] R 1 ~R 10 Examples of the alkyl group having 1 to 4 carbon atoms in R 1 and R 10 include a methyl group, an ethyl group, a propyl group, a tert-butyl group, etc. In polymer (A1), from the viewpoint of improving solubility, it is preferable that at least one of R 1 and R 10 is an alkyl group, it is more preferable that R 1 and R 10 are tert-butyl groups. By having a bulky substituent in at least one of R 1 and R 10 , aggregation of the polymer due to π-π stacking, etc. is suppressed, and the solubility in the solvent is improved. On the other hand, R 1 ~R 8 are each independently preferably a hydrogen atom or a methyl group, and more preferably a hydrogen atom.
[0038] Polymer (A1) has Ar having an anion exchange group 1 and a spirobifluorene skeleton are alternately repeated. In the polymer (A1), each element constituting the main chain skeleton belongs to an aromatic ring or is a spiro atom having no hydrogen atom, and since the main chain skeleton has no ether bond, decomposition in the presence of alkali or radicals is suppressed, and it has excellent chemical durability. Further, the spirobifluorene skeleton has a structure in which two fluorene are twisted at substantially right angles via a spiro atom, and since the fluorene skeleton constitutes the main chain, the entire main chain is in a state having a large number of bends. Therefore, since the planarity of the main chain is lowered, π-π stacking is inhibited, and it also has excellent solubility in a solvent and excellent handleability when filling a porous substrate.
[0039] The synthesis method of the polymer (A1) is not particularly limited, but as a preferred example, the method of Scheme A1 below can be mentioned.
[0040]
Chemical formula
[0041] In the example of Scheme A1 above, a compound (C) having a brominated spirobifluorene skeleton is synthesized from a compound (B) having a desired substituent R b (Steps (i) to (vii)). Separately from this, a compound (E) which is a precursor of Ar 1 in the general formula (1-1) is synthesized by reacting a bromide (D) having a desired aromatic ring (benzene ring in the example of Scheme A1) with bis(pinacolato)diborane (Step (viii)). Note that the reaction conditions for each of the above steps may be referred to known reactions. Next, after dissolving the compound (C) and the compound (E) in an organic solvent such as 1,4-dioxane or toluene, a palladium catalyst such as palladium(II) acetate, a phosphine ligand such as Sphos, and a base such as tripotassium phosphate are mixed and heated with stirring under a nitrogen atmosphere to obtain a copolymer (step (ix)). Finally, by introducing a desired anion exchange group, a polymer represented by the general formula (1-1) is obtained (~ step (xi)).
[0042] · Polymer (A2) Polymer (A2) has a repeating unit represented by the following general formula (1-b).
[0043]
Chemical formula
[0044] Polymer (A2) is a polymer having two or more of the above structural units (1-b), and is a compound with an all-aromatic main chain. Since polymer (A2) has such a structure, it has excellent durability against alkalis, radicals, etc.
[0045] Ar in polymer (A2) 2 is preferably a phenylene group, a biphenylene group, or a terphenylene group, and more preferably a p-phenylene group (the following formula (Ar-1)), a 4,4'-biphenylene group (the following formula (Ar-2)), or a 4,4''-terphenylene group (the following formula (Ar-3)).
[0046]
Chemical formula
[0047] Ar 2When it is a p-phenylene group, 4,4'-biphenylene group, or 4,4''-terphenylene group, the polymer (A2) is likely to have a zigzag arrangement of the main chain skeleton as shown in the following formula. The following formula represents, by way of example, Ar 2 shows the case where it is a p-phenylene group, but the same applies to the 4,4'-biphenylene group or 4,4''-terphenylene group. As shown in the following formula, the polymer (A2) is likely to have a zigzag arrangement of the main chain skeleton, and further each R a is likely to be arranged outside the fold of the skeleton. Therefore, intermolecular aggregation due to folding of the main chain and the like is suppressed. As a result, it becomes a polymer capable of forming an electrolyte membrane excellent in ion conductivity.
[0048]
Chemical formula
[0049] The group R having an anion exchange group in the polymer (A2) a is, among others, preferably a group represented by the following formula (R a -1).
[0050]
Chemical formula
[0051] In the group represented by the above formula (R a -1), the carbon atom adjacent to the benzene ring constituting the main chain is a quaternary carbon atom. Therefore, π-π stacking between the polymers (A2) is suppressed. As a result, aggregation of the polymer (A2) is suppressed, making it easy to dissolve in a solvent and having excellent handling properties during film formation and the like. p2 represents {(the number of carbon atoms from R b2 to the quaternary carbon atom)-1}, and it may be appropriately adjusted within the range of 1 or more and 20 or less. Among them, 1 to 15 is preferable, 1 to 12 is more preferable, and 1 to 6 is still more preferable.
[0052] The method for synthesizing the polymer (A2) is not particularly limited, and as a preferred example, the method of Scheme A2 below can be mentioned.
[0053] [Chemical formula] However, X and X 1 represent halogen atoms, and Ar 2 , and p2 are as described above. As the halogen atom of X 1 , Br is preferred.
[0054] In the example of Scheme A2 above, first, compound (H) and compound (I) having the desired Ar 2 are dissolved in a palladium catalyst such as tetrakis(triphenylphosphine)palladium(0), a carbonate such as sodium hydrogen carbonate, and a solvent such as tetrahydrofuran or water, and heated and stirred to obtain a polymer having a structural unit represented by (J). Next, a desired anion exchange group is introduced into the polymer (J) to obtain the polymer (A2). In Scheme A2 above, a quaternary ammonium is introduced, but other ionic functional groups can also be introduced accordingly. The reaction conditions for each of the above steps may be determined with reference to known reactions.
[0055] · Polymer (A3) In the repeating unit represented by the general formula (1), the polymer (A3) has a partial structure represented by the following formula (2) at both ends. In other words, the Ar 2 is a divalent group containing an aromatic ring having a fluoro group (-F) at the α-position of the terminal carbon atom. Here, the terminal of Ar 2 refers to the carbon atom that binds to Ar 2 . The wavy line represents the bond to Ar 1 , and the dotted line indicates that a part of the aromatic ring is omitted. 1
[0056] [Chemical formula]
[0057] Polymer (A3) has Ar with an anion exchange group 1 and Ar having a partial structure (2) containing a fluoro group (-F) 2 which has an alternately arranged structure. Ar constituting the main chain 1 and Ar 2 each have an aromatic group and are excellent in chemical durability against alkalis, radicals, etc. Further, Polymer (A3) has Ar having an ion exchange group linked via an alkyl chain at the side chain terminal 1 and Ar having no ion exchange group 2 which are alternately arranged. Because of having such a structure, it is excellent in solubility in a solvent and ion conductivity. Further, the reactivity between the compound having the partial structure (2) and the compound represented by the following formula (4) described later is high, and a polymer having a higher molecular weight can be produced. By using the polymer having a higher molecular weight, it is also possible to form a film having more excellent durability.
[0058] Ar 2 For example, as in the following formula (b-1), it may have two partial structures (2) in one ring structure (for example, a benzene ring), or as in the following formula (b-2), one C-F bond may constitute two partial structures (2). Further, in the case of the above-mentioned chain-like polycyclic hydrocarbon, each of the two ring structures of the chain-like polycyclic hydrocarbon may have one partial structure (2), and those rings may be linked directly or via the above-mentioned linking group, or one of the plurality of ring structures may have two partial structures (2). It is preferable that Ar in Polymer (A3) does not have a spiro atom. 2
[0059] In Polymer (A3), from the viewpoint that an electrolyte membrane excellent in ion conductivity and film-forming property and excellent in chemical durability and film strength can be formed, it is preferable that the above-mentioned Ar 2 is one or more selected from the following formula (d1) to the following formula (d9). The wavy line indicates a bond with Ar 1
[0060]
Chemical formula
[0061] The above R d Examples of the halogeno group in R include a fluoro group, a chloro group, a bromo group, and an iodo group. Among these, a fluoro group is preferred. Further, examples of the organic group in the above R d include a linear or branched alkyl group having 1 to 20 carbon atoms (excluding the carbon atoms of the substituent) which may have a substituent (e.g., a halogeno group).
[0062] From the viewpoint of ease of production, the above Ar 2 is preferably represented by the following formulas (d10) to (d14). The wavy line indicates a bond to Ar 1 .
[0063]
Chemical formula
[0064] The method for synthesizing the polymer (A3) is not particularly limited, and a suitable example is the method of the following Scheme A3.
[0065]
Chemical formula
[0066] Since the X 1 of the compound (4) and the hydrogen atom of the following partial structure (5a) possessed by Ar 2 of the compound (5) are excellent in reactivity, a high molecular weight ionic conductive polymer can be synthesized relatively easily.
[0067] [Chemical formula]
[0068] In the above-mentioned scheme A3, first, a compound (4) having a desired Ar 3 and a compound (5) having a desired Ar 2 are prepared. Then, these compounds are reacted, for example, in a solvent in the presence of a Pd complex, a ligand, a carboxylic acid (RCO2H) and a base at 80 to 140 °C for 1 to 48 hours to obtain a polymer having a structural unit (3).
[0069] Next, a polymer (A3) is obtained by introducing a desired ion-exchange group into the polymer having a structural unit (3). Thus, the polymer (A3) can be easily produced with extremely few synthesis steps using the compound (4) and the compound (5) as raw materials.
[0070] · Polymer (A4) The polymer (A4) has a repeating unit represented by the following general formula (1-4).
[0071] [Chemical formula] However, the ring Ar 11 and the ring Ar 12 are rings condensed with a benzene ring and are condensed rings of three or more rings having an aromatic attribute as a whole, and Ar 1 is the same as that in the general formula (1).
[0072] The polymer (A4) has a structure in which Ar 1 having an anion-exchange group and Ar 2 composed of three or more condensed rings are alternately repeated. Generally, a polymer containing many ion-exchange groups tends to swell, but the polymer (A4) has excellent swelling resistance due to the alternating repetition of Ar 1 and Ar 2 and the π-π stacking of three or more condensed rings.
[0073] Ring Ar 11 and Ring Ar 12 is an aromatic ring which may have a heteroatom. Examples of the heteroatom include N (nitrogen atom), O (oxygen atom), and S (sulfur atom). Ring Ar 11 and Ring Ar 12 The condensed ring containing Ring Ar and Ring Ar is preferably a condensed ring of 3 or more rings from the viewpoint of swelling resistance. On the other hand, from the viewpoint of increasing the ion exchange capacity of the polymer (A4), a condensed ring of 5 or less rings is preferable, and a condensed ring of 4 or less rings is more preferable. Preferable specific examples of the condensed ring include the following. The wavy line indicates the bond with Ar 1 . Also, the hydrogen atom may be substituted with a group having no anion exchange group.
[0074]
Chemical formula
[0075] The polymer (A4) is preferably synthesized by preparing a precursor (1-5) having a repeating unit represented by the following general formula (1-5) and eliminating the substituent (TL) after filling the porous substrate.
[0076]
Chemical formula
[0077] Polymer (A4) has excellent swelling resistance as described above. Therefore, it has a problem of being difficult to dissolve in various organic solvents and having poor handleability during processing. In the above precursor, a substituent (TL) represented by the above general formulas (LT1) to (LT3), which is bulky and can be relatively easily removed by the action of heat or light, is introduced at a site corresponding to the condensed ring of polymer (A4). In precursor (1-5), the π-π stacking of the hydrophobic part is inhibited by the substituent, and the solubility in various organic solvents is improved. Therefore, the above precursor has excellent handleability and is easy to fill into a porous substrate. Note that the substituent (TL) can be removed by heating or light irradiation.
[0078] The synthesis method of the above precursor is not particularly limited, but as a preferred specific example, the method of the following Scheme A4 can be mentioned.
[0079]
Chemical formula
[0080] An example of each step of the above Scheme A4 will be described. Step (i): Prepare a toluene solution of the above compound (1), add diethyl azodicarboxylate (DEAD), and heat to reflux to obtain the above compound (2). Step (ii): Separately, prepare an N,N-dimethylformamide (DMF) solution of the above compound (3), add bis(pinacolato)diboron, potassium acetate (KOAc), and [1,1'-bis(diphenylphosphino)ferrocene]palladium(II) dichloride (Pd(dppf)Cl2), and heat to 90 °C to obtain the above compound (4). Step (iii): Add tripotassium phosphate (K3PO4) and tetrakis(triphenylphosphine)palladium (Pd(PPh3)4) to the toluene solution of the obtained above compound (2) and the above compound (4), and heat to 100 °C for polymerization to obtain the above compound (5). Step (iv) In chlorobenzene, the obtained compound (5), N-bromosuccinimide (NBS), and azobisisobutyronitrile (AIBN) are added and mixed, and heated to 110 °C to obtain the above compound (6). Step (v): The obtained compound (6) is heated to 50 °C in a mixed solvent of DMF / THF (tetrahydrofuran) to obtain a precursor represented by the above chemical formula (7).
[0081] Mw and Mw / Mn vary greatly depending on the synthesis conditions. There are various methods for controlling the Mw and Mw / Mn of polymers, but mainly methods for controlling the equivalent amounts and synthesis concentrations of substrates and initiators are adopted. Since the polymers described in this specification are produced by polymerization using a catalyst such as palladium, it is necessary to appropriately set the catalyst concentration and substrate concentration. As a result of various studies, it has been found that by controlling the reaction conditions in the range where the catalyst concentration is 0.3 to 1.5 mol% with respect to the synthesis substrate and the synthesis concentration of the substrate is 0.2 M to 0.4 M, polymers having Mw and Mw / Mn in the present invention can be accurately obtained. Note that since the collision frequency of molecules decreases as the synthesis concentration becomes dilute, it is necessary to appropriately extend the heating time.
[0082] [Use of electrolyte membrane] [Catalyst-coated electrolyte membrane] The electrolyte membrane of the present invention can be used as a catalyst-coated electrolyte membrane in which one side or both sides are coated with a catalyst. For example, in an electrolyte membrane used for water electrolysis, an anode catalyst is disposed on one surface as an anode, and a cathode catalyst is disposed on the other surface as a cathode. The anode catalyst is preferably a metal or a metal alloy. The metal or metal alloy can be appropriately selected from known ones. For example, platinum, cobalt, nickel, palladium, iron, silver, gold, copper, iridium, molybdenum, rhodium, chromium, tungsten, manganese, ruthenium, metal compounds thereof, metal oxides, and alloys containing two or more of these metals can be mentioned. The cathode catalyst is preferably a metal or a metal alloy. The metal or metal alloy can be appropriately selected from known ones. For example, platinum, cobalt, nickel, palladium, iron, silver, gold, copper, iridium, molybdenum, rhodium, chromium, tungsten, manganese, ruthenium, these metal compounds, metal oxides, and alloys containing two or more of these metals can be mentioned. Examples of the method for forming the catalyst layer include coating methods such as pulse spray coating method, ultrasonic spray coating method, die coater coating method, bar coater coating method, and electrode transfer method coating method. Note that depending on the coating method, a drying process may be included.
[0083] <Proton Exchange Membrane, Anion Exchange Membrane for Water Electrolysis, and Water Electrolysis Device> The catalyst-coated electrolyte membrane of the present invention has water electrolysis performance, particularly anion exchange type water electrolysis performance. The anion exchange membrane type water electrolysis performance means that a catalyst layer in which metal powder having hydrogen generation ability is dispersed in an ionomer is formed on the cathode side of an electrolyte membrane having an anion exchange group, and on the other anode side, a catalyst layer in which metal powder having oxygen generation ability is dispersed in an ionomer is formed. When an alkaline solution is passed through the electrochemical cell and an electric current is passed from a power source to the electrochemical cell including the electrolyte membrane ion-exchanged with OH ions by the alkaline solution and the ionomer, it means that water electrolysis is possible without a large increase in voltage. Specifically, carbon supporting platinum or carbon supporting a platinum ruthenium alloy is generally used for the hydrogen generation catalyst, and iridium oxide is generally used for the oxygen generation catalyst on the other side. It is sufficient that when 1 mol / L potassium hydroxide is used in the alkaline solution and the electrolysis performance is 1 A / cm2 at 80°C for the electrochemical cell, the voltage is 2.0 V or less, preferably 1.7 V to 1.8 V, and particularly preferably 1.78 V or less. The ion exchange capacity represents the amount of ions that an ion exchange resin can adsorb. The higher this value, the higher the ion conductivity, but the water content also increases, the electrolyte membrane swells, and the gas barrier property deteriorates. Therefore, 1.0 mmol / g to 2.0 mmol / g is preferable, particularly preferably 1.2 mmol / g to 1.9 mmol / g, and most preferably 1.3 to 1.7 mmol / g. The water electrolysis device equipped with the above anion exchange type electrolyte membrane for water electrolysis can be used as an excellent hydrogen generation device, especially because of its high alkali durability.
Example
[0084] Hereinafter, the present invention will be described more specifically with reference to examples. Note that these descriptions do not limit the present invention, and it can be appropriately changed without departing from the gist. In [Chemical Formula 1-2] and [Chemical Formula 1-3], n represents the number of repetitions of the polymer structural unit. Also, regarding the Mw and Mn of the polymer, since it is difficult to measure the aminopolymer with an amino group at the end, the one before amination will be described. However, since the influence on the results is minor, it is considered that they can be regarded as the same.
[0085] <Example 1> [Step 1: Synthesis of Substrate (1-1)] Into a four-necked flask, n-tetrabutylammonium chloride (3.04 g), 1,10-dichlorodecane (1097 mmol), and 2,7-dibromofluorene (109.7 mmol) were added to an aqueous solution of sodium hydroxide (200 g) (600 mL) in this two-necked flask with a syringe, and stirred under nitrogen. Then, after reacting at 90 °C under nitrogen for 90 minutes, the obtained reaction solution was cooled to room temperature (25 °C). The organic phase in the cooled reaction solution was extracted with toluene (200 mL) using a separating funnel, and washed with 1 M hydrochloric acid (50 mL) and saturated brine (200 mL × 2). The toluene in the obtained organic phase was removed with an evaporator, and further, unreacted 1,10-dichlorodecane was removed at 180 °C under reduced pressure. The obtained residue was applied to a silica gel column (developing solvent: hexane) to obtain the target substrate (1-1) (68.7 mmol) of Step 1 of Example 1. 1H-NMR (400 MHz, CDCl3): δ 7.51 (2H, d), δ 7.45 - 7.42 (4H, m), δ 3.51 - 3.47 (4H, t), δ 1.91 - 1.87 (4H, m), δ 1.75 - 1.68 (4H, m), 1.35 - 1.33 (4H, m), δ 1.23 - 1.05 (20H, m), δ 0.58 - 0.53 (4H, m)
[0086] [Chemical formula 1-1] TIFF2025100998000026.tif63153
[0087] [Step 2: Synthesis of Polymer (1-2)] Into a separable flask, compound (1-1) (57.7 mmol) and tetrahydrofuran (180 mL) were added, and the mixture was stirred while bubbling with nitrogen (20 mL / min) for 30 min. Next, cesium carbonate (173 mmol), pivalic acid (57.7 mmol), tris(2-methoxyphenyl)phosphine (407 mg), Pd2(dba)3 (291 mg), and 1,2,4,5-tetrafluorobenzene (57.7 mmol) were added and heated. After reacting these mixtures at room temperature (25°C) for 15 min under nitrogen, the reaction was carried out at 85°C for 12 h. Then, 1 M hydrochloric acid (100 mL) and toluene (600 mL) were added to the obtained reaction product (solid content), and the mixture was stirred at 60°C for 30 min. After removing the insoluble matter by vacuum filtration, the organic phase was extracted with a separatory funnel. The extracted organic phase was washed with 1 M hydrochloric acid and saturated brine, and then the liquid component in the obtained organic phase was removed by an evaporator and dried to dryness. The obtained residue was dissolved in toluene and reprecipitated in methanol. The obtained precipitate was filtered to remove the liquid component. The obtained solid content was vacuum dried to obtain the target polymer (1-2) of Step 2 of Example 1. 1H-NMR (400 MHz, CDCl3): δ 7.92 - 7.90 (2H, d), δ 7.55 - 7.51 (4H, m), δ 3.51 - 3.47 (4H, t), δ 2.04 (4H, br), δ 1.71 (4H, m), 1.37 - 1.33 (4H, m), δ 1.19 - 1.10 (20H, m), δ 0.78 (4H, br) GPC: Mw = 209299, Mn = 32299, Mw / Mn = 6.48
[0088] [Chemical Formula 1-2] TIFF2025100998000027.tif76153
[0089] [Process 3: Synthesis of Amino Polymer (1-3)] Weighed 2 g of the polymer (1-2) obtained in Step 2 into a pressure-resistant test tube, added 20 mL of chlorobenzene, and dissolved it. Then, 10 mL of a 25% by mass trimethylamine methanol solution was added, and the mixture was stirred at 100°C for 3 hours. After that, 10 mL of dimethyl sulfoxide was added, and the mixture was stirred for another 3 hours. After removing most of the chlorobenzene in the reaction solution with an evaporator, 20 mL of dimethyl sulfoxide and 10 mL of a 25% by mass trimethylamine methanol solution were added, and the mixture was stirred at 100°C for 2 hours. The dimethyl sulfoxide in the obtained reaction solution was removed by an evaporator on a 70°C water bath and dried to dryness. Water was added to the dried residue, filtered, water was added to the obtained solid content, and the mixture was stirred at 80°C. Then, it was cooled to room temperature (25°C), filtered, and the obtained solid content was vacuum dried to obtain 2.1 g of the target amino polymer (1-3) in Step 3 of Example 1. 1H-NMR (400 MHz, CD3OD): δ8.07 (2H, m), δ7.67 (4H, m), δ3.29 (4H, m), δ3.10 (18H, t), δ2.19 (4H, br), δ1.75 (4H, m), δ1.32 - 1.14 (24H, m), δ0.71 (4H, br)
[0090] [Chemical Formula 1-3] TIFF2025100998000028.tif80153
[0091] [Example 2] [Step 1: Synthesis of Substrate (1-1)] The target compound in Step 1 of Example 1 was used to conduct the synthesis of the next step. [Step 2: Synthesis of Polymer (1-2)] In Example 2, the synthesis was carried out in the same manner except that 160 mL of tetrahydrofuran, 350 mg of tris(2-methoxyphenyl)phosphine, and 203 mg of Pd2(dba)3 were added in Step 2, and the heating time was 22 hours, to obtain the target polymer (1-2) in Step 2 of Example 2. 1H-NMR(400MHz,CDCl3):δ7.91(2H,d),δ7.55-7.51(4H,m),δ3.51-3.47(4H,t),δ2.06(4H,br),δ1.72-1.71(4H,m),1.35-1.33(4H,m),δ1.20-1.10(20H,m),δ0.77(4H,br) GPC:Mw=267771,Mn=39599,Mw / Mn=6.76
[0092] [Step 3: Synthesis of Amino Polymer (1-3)] In Example 2, the same operations as in Step 3 of Example 1 were carried out except that the polymer added in Step 3 of Example 1 was changed to the polymer (1-2) in Step 2 of Example 2, to obtain the target amino polymer (1-3) in Step 3 of Example 2. 1H-NMR(400MHz,CD3OD):δ8.05(2H,m),δ7.65(4H,m),δ3.29(4H,m),δ3.08(18H,t),δ2.19(4H,br),δ1.72-1.70(4H,m),δ1.30-1.18(24H,m),δ0.73(4H,br)
[0093] [Example 3] [Step 1: Synthesis of Substrate (1-1)] The target compound in Step 1 of Example 1 was used to carry out the synthesis in the next step. [Step 2: Synthesis of Polymer (1-2)] In Example 3, the synthesis was carried out in the same manner except that 160 mL of tetrahydrofuran was added in Step 2 of Example 1 and the heating time was 12 hours, to obtain the target polymer (1-2) in Step 2 of Example 3. 1H-NMR(400MHz, CDCl3): δ 7.92(2H, d), δ 7.55(4H, m), δ 3.51 - 3.47(4H, t), δ 2.05(4H, br), δ 1.72 - 1.69(4H, m), 1.37 - 1.32(4H, m), δ 1.20 - 1.10(20H, m), δ 0.77(4H, br) GPC: Mw = 357158, Mn = 66634, Mw / Mn = 5.36
[0094] [Step 3: Synthesis of Amino Polymer (1 - 3)] The same operations as in Step 3 of Example 1 were carried out except that the polymer added in Step 3 of Example 1 was changed to the polymer obtained in Step 2 of Example 3, and the target amino polymer (1 - 3) of Step 3 of Example 3 was obtained. 1H-NMR(400MHz, CD3OD): δ 8.07 - 8.06(2H, m), δ 7.67(4H, m), δ 3.31 - 3.30(4H, m), δ 3.11(18H, t), δ 2.20(4H, br), δ 1.74(4H, m), δ 1.35 - 1.14(24H, m), δ 0.74(4H, br)
[0095] [Comparative Example 1] [Step 1: Synthesis of Substrate (1 - 1)] The target compound of Step 1 of Example 1 was used to carry out the synthesis of the next step. [Step 2: Synthesis of Polymer (1 - 2)] Synthesis was carried out in the same manner except that the tetrahydrofuran added in Step 2 of Example 1 was 160 mL and the heating time was 6.5 hours, and the target polymer (1 - 2) of Step 2 of Comparative Example 1 was obtained. 1H-NMR(400MHz, CDCl3): δ 7.92(2H, d), δ 7.55(4H, m), δ 3.51 - 3.47(4H, t), δ 2.05(4H, br), δ 1.72 - 1.71 (4H, m), 1.37 - 1.33(4H, m), δ 1.19 - 1.10(20H, m), δ 0.77(4H, br) GPC: Mw = 160356, Mn = 43694, Mw / Mn = 3.67
[0096] [Step 3: Synthesis of Amino Polymer (1 - 3)] The same operations as in Step 3 of Example 1 were carried out, except that the polymer added in Step 3 of Example 1 was changed to the polymer obtained in Step 2 of Comparative Example 1, to obtain the target aminopolymer (1-3) in Step 3 of Comparative Example 1. 1H-NMR(400MHz,CD3OD):δ8.05(2H,m),δ7.65-7.62(4H,m),δ3.29(4H,m),δ3.08(18H,t),δ2.18(4H,br),δ1.72(4H,m),δ1.30-1.11(24H,m),δ0.74(4H,br)
[0097] <Comparative Example 2> [Step 1: Synthesis of Substrate (1-1)] The target compound in Step 1 of Example 1 was used to carry out the synthesis of the next step. [Step 2: Synthesis of Polymer (1-2)] In Step 2 of Example 1, the synthesis was carried out in the same manner except that tris(2-methoxyphenyl)phosphine was 350 mg, Pd2(dba)3 was 203 mg, and the heating time was 28 hours, to obtain the target polymer (1-2) in Step 2 of Comparative Example 2. 1H-NMR(400MHz,CDCl3):δ7.91(2H,d),δ7.56(4H,m),δ3.51-3.47(4H,t),δ2.16-2.13(4H,br),δ1.72-1.71(4H,m),1.37-1.33(4H,m),δ1.19-1.10(20H,m),δ0.78(4H,br) GPC:Mw=435348,Mn=44835,Mw / Mn=9.71
[0098] [Step 3: Synthesis of Aminopolymer (1-3)] The same operations as in Step 3 of Example 1 were carried out, except that the polymer added in Step 3 of Example 1 was changed to the polymer obtained in Step 2 of Comparative Example 2, to obtain the target aminopolymer (1-3) in Step 3 of Comparative Example 2. 1H-NMR (400 MHz, CD3OD): δ 8.05 (2H, m), δ 7.65 (4H, m), δ 3.29 (4H, m), δ 3.08 (18H, t), δ 2.17 (4H, br), δ 1.72 - 1.70 (4H, m), δ 1.30 - 1.11 (24H, m), δ 0.70 (4H, br)
[0099] <Film-forming property test> In a 30 ml vial, 0.3 g of the amino polymers prepared in Examples 1 to 3, Comparative Examples 1 and 2 were weighed respectively, and 15 ml of dimethyl sulfoxide was added to each. Then, a polymer solution for film formation was prepared by heating and stirring at 60 °C for 24 h using a hot stirrer. At that time, when it was completely dissolved, it was evaluated as ○, and when there was undissolved residue, it was evaluated as ×. The results are shown in Table 1. Regarding Comparative Example 2, it hardly dissolved in the solvent.
[0100] <Alkali durability test> The polymer solutions for film formation prepared in the above film-forming property test were each dropped by 3 mL onto a 5 cm × 5 cm glass substrate placed on a hot plate. After the dropping was completed, the temperature was raised to 80 °C and heated for 1 h to prepare a cast film. After cooling to room temperature, the glass substrate was put into a tray filled with water, and the cast film was peeled off from the substrate. The peeled cast film was dried under reduced pressure at 80 °C for 24 h. The prepared cast film and 20 mL of 8M NaOH aqueous solution were put into a high-density polyethylene container and heated at 80 °C for 80 h in a constant temperature bath. The film state after cooling to room temperature was visually confirmed, and those with undegraded films were evaluated as ○, and those with degraded films were evaluated as ×. Also, those for which films could not be prepared in the film-forming property test were designated as ―. The results are shown in Table 1.
[0101]
Table 1
[0102] From Table 1, the polymers prepared in Examples 1 to 3 were well dissolved in the solvent, and a polymer solution for film formation was successfully prepared. However, the polymer shown in Comparative Example 2 did not dissolve. This is presumably due to the large Mw and Mw / Mn. Also, when the cast films made of the polymers prepared in Examples 1 to 3 and Comparative Example 1 were subjected to an alkali durability test, they disintegrated in Comparative Example 1. This is presumably because the Mw of the polymer was small and the film strength was insufficient. From the above results, it was found that there is a suitable range for both Mw and Mw / Mn in the polymers used for anion exchange membranes.
Industrial Applicability
[0103] According to the present invention, an electrolyte membrane excellent in solubility, that is, having good film-forming properties and excellent alkali durability can be realized. This electrolyte membrane is useful for the water electrolysis method, particularly the anion exchange membrane type water electrolysis method, and can efficiently generate hydrogen.
Claims
1. An electrolyte membrane using a polymer that satisfies the following formula (Equation 1) with respect to Mw (weight average molecular weight). 【Number 1】
2. The electrolyte membrane according to Claim 1, using a polymer in which Mw / Mn (molecular weight distribution index) satisfies the following formula (Equation 2). 【Number 2】
3. The electrolyte membrane according to Claim 1 or 2, using a polymer that satisfies the following formula (Equation 3) with respect to Mn (number average molecular weight). [Number 3]
4. The electrolyte membrane according to Claim 1 or 2, having a pore filling structure.
5. The electrolyte membrane according to Claim 1 or 2, wherein the polymer has a structure represented by the following formula (Chemical Formula 1). 【Chemical 1】 However, Ar 1 is an aromatic group having an ion-exchange group or a group in which aromatic rings having ion-exchange groups are linked via single bonds, and a plurality of Ar 1 may be the same or different, Ar 2 is an aromatic group having no ion-exchange group, or a group in which two or more aromatic rings having no ion-exchange group are linked via a single bond or a spiro atom, and a plurality of Ar 2 may be the same or different, Ar 1 The aromatic ring possessed by Ar 2 and the aromatic ring possessed by Ar are connected via a single bond.
6. A catalyst-coated electrolyte membrane in which a catalyst is coated on the electrolyte membrane according to Claim 1 or 2.
7. The electrolyte membrane for water electrolysis according to Claim 1 or 2.
8. The anion exchange type water electrolysis electrolyte membrane according to Claim 1 or 2.
9. A water electrolysis device using the electrolyte membrane according to Claim 1 or 2.
10. A method for producing hydrogen using the electrolyte membrane according to Claim 1 or 2.
Citation Information
Patent Citations
JP2016-442424A
Polymer, electrolyte membrane, and solid polymer fuel cell
JP2018135487A
Polymer, precursor, method for producing polymer, electrolyte membrane, fuel cell, water electrolysis and electrolysis technique
JP2021042351A
Cited By
Polymer, electrolyte membrane, membrane electrode assembly, fuel cell, and water electrolysis device
WO2026004900A1